The early impact of COVID-19 on job losses among Black women in the United States - Michelle Holder; Janelle Jones; Thomas Masterson (Levy Economics Institute of Bard College, 2020)
The COVID-19 pandemic seemingly appeared out of nowhere but changed nearly everything. As the pandemic unfolded, industries deemed nonessential were leveled. Many occupations in these industries are low-wage, and women constitute a greater share of America's low-wage labor force than men. Even as some workers were able to do their jobs from their homes, a high proportion of "essential workers" were African American, other people of color, women, and an intersection of these groups - women of color. The goal of this paper is to closely examine the contours, depth, and causes of COVID-19's impact on Black women's employment in the United States through the lenses of both feminist economic theory and stratification economics.
Keywords: J15; J16; J21; 330; Occupational Segregation; Racial Discrimination; Gender Discrimination; COVID-19